STUDY ON EFFECT OF pH AND METAL CONCENTRATION ON THE SYNTHESIS OF DIMENSIONALLY STABLE ANODE GAPHITE/La2O3-ZrO2 AND GAPHITE/RuO2-TiO2 - Suyanta Suyanta; Agus Kuncaka (Indonesian Journal of Chemistry, 2006)
The objective of this research is to study the effect of pH and metal concentration toward the mass of metal oxides coated on gaphite in the synthesis of dimensionally stable anode (DSA) gaphite/La2O3-ZrO2 and gaphite/RuO2-TiO2. The synthesis of those  DSA was done by thermal decomposition technique. The solution containing metal ion to be coated (as its oxides) on the gaphite, followed by heating. Those spraying and heating were repeated up to ten times, so that it was expected that all of gaphite surface was covered by the metal oxides. It was concluded that the mass of metal oxides coated on the gaphite was affected by the pH and concentration of metals in the solutian to be sprayed. Treatment by using solution at pH of 4 and 6 produced  more in mass of metal oxides mixture than  using solution of 1 and 2 on pHs. DSA gaphite/La2O3-ZrO2 produced by treatment using solution of 4 and 6 on pHs contained more in mass of La2O3 than of ZrO2; meanwhile DSA gaphite/RuO2-TiO2 produced in this research (for all of treatment) contained more in mass of RuO2 than of TiO2.